2016
DOI: 10.1128/jvi.03033-15
|View full text |Cite
|
Sign up to set email alerts
|

TRIM5α Degradation via Autophagy Is Not Required for Retroviral Restriction

Abstract: TRIM5␣ is an interferon-inducible retroviral restriction factor that prevents infection by inducing the abortive disassembly of capsid cores recognized by its C-terminal PRY/SPRY domain. The mechanism by which TRIM5␣ mediates the disassembly of viral cores is poorly understood. Previous studies demonstrated that proteasome inhibitors abrogate the ability of TRIM5␣ to induce premature core disassembly and prevent reverse transcription; however, viral infection is still inhibited, indicating that the proteasome … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
25
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 44 publications
3
25
0
Order By: Relevance
“…As another example of a selective autophagy target, we tested whether TRIM17 could affect the autophagic targeting of TRIM5α, which has recently been reported to be protected from lysosomal degradation by autophagy inhibition (Imam et al, 2016). In agreement with these findings, mCherry-eYFP-TRIM5α showed primarily 'red' and not green fluorescence in cells, indicating its presence within acidified compartments ( Fig.…”
Section: Trim17 Inhibits Degradation Of Selective Autophagy Targetssupporting
confidence: 72%
“…As another example of a selective autophagy target, we tested whether TRIM17 could affect the autophagic targeting of TRIM5α, which has recently been reported to be protected from lysosomal degradation by autophagy inhibition (Imam et al, 2016). In agreement with these findings, mCherry-eYFP-TRIM5α showed primarily 'red' and not green fluorescence in cells, indicating its presence within acidified compartments ( Fig.…”
Section: Trim17 Inhibits Degradation Of Selective Autophagy Targetssupporting
confidence: 72%
“…Notably, while the manuscript was in revision, a paper by Fletcher et al observed that TRIM5␣ assembly around restrictionsensitive viral cores triggers TRIM5␣ autoubiquitination with K63-linked ubiquitin, which drives the proteasomal degradation of TRIM5␣ (45). Our data using DUB fusions in this study are entirely consistent with such a noncanonical function of K63-linked ubiquitin and are also consistent with our previous observation that all aspects of TRIM5␣ restriction are insensitive to depletion of the key autophagic mediators Beclin1 and Atg5 (34). Such a model can also reconcile prior studies that observe that proteasomal inhibition prevents TRIM5␣-mediated core disassembly (14,17) and the degradation of TRIM5␣ observed in response to saturating levels of restriction-sensitive virus (19).…”
Section: Discussionsupporting
confidence: 91%
“…In simian cells, it was observed following viral fusion that HIV Gag from incoming viral particles might be selectively targeted to autophagosomal degradation by the antiviral restriction factor TRIM5a (83). Although whether functional autophagy is required for TRIM5a-mediated HIV restriction is a matter of debate (84), these results suggest that specific adaptors might be required to target HIV Gag to autophagosomes. In the present study, we did not observe any colocalization between Gag and LC3 in productively infected DC and cells expressing Gag in the absence of other viral proteins.…”
Section: Discussionmentioning
confidence: 99%